2016
DOI: 10.5194/angeo-34-815-2016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the generation and propagation of ultralow-frequency waves by artificial ionospheric F region modulation at different latitudes

Abstract: Abstract. Powerful high-frequency (HF) radio waves can be used to efficiently modify the upper-ionospheric plasmas of the F region. The pressure gradient induced by modulated electron heating at ultralow-frequency (ULF) drives a local oscillating diamagnetic ring current source perpendicular to the ambient magnetic field, which can act as an antenna radiating ULF waves. In this paper, utilizing the HF heating model and the model of ULF wave generation and propagation, we investigate the effects of both the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…By considering the characteristics of the magnetic field and radio wave propagation in the mid-latitude ionosphere, Sharma et al [70] studied the excitation of ELF waves by the ICD method in the mid-latitude region and its propagation in the ionosphere and magnetosphere. Xu et al [71] studied the generation and propagation of ULF waves modulated by the ICD mechanism under different background ionospheric parameters and modulation frequencies through numerical simulation. Streltsov et al [72] found that the intensity of ELF waves was significantly enhanced when modulated with the frequency of Schumann resonance.…”
Section: Ionospheric Current Drivementioning
confidence: 99%
“…By considering the characteristics of the magnetic field and radio wave propagation in the mid-latitude ionosphere, Sharma et al [70] studied the excitation of ELF waves by the ICD method in the mid-latitude region and its propagation in the ionosphere and magnetosphere. Xu et al [71] studied the generation and propagation of ULF waves modulated by the ICD mechanism under different background ionospheric parameters and modulation frequencies through numerical simulation. Streltsov et al [72] found that the intensity of ELF waves was significantly enhanced when modulated with the frequency of Schumann resonance.…”
Section: Ionospheric Current Drivementioning
confidence: 99%
“…The absorption in the D/E region decreases with the increase of strength and dip angle of the geomagnetic field, and increases with ionospheric electron density and collision frequency. Xu X et al (2016) conducted numerical simulations of the generation and propagation of ultralow-frequency (ULF) waves by artificial ionospheric F region modulation at different latitudes. Their numerical simulations show the effects of background ionospheric parameters and modulation frequency on the generation and propagation of ULF waves.…”
Section: Radio Wave Propagation In the Ionospherementioning
confidence: 99%
“…Xu X et al (2016) conducted numerical simulations of the generation and propagation of ultralow‐frequency (ULF) waves by artificial ionospheric F region modulation at different latitudes. Their numerical simulations show the effects of background ionospheric parameters and modulation frequency on the generation and propagation of ULF waves.…”
Section: Radio Wave Propagation In the Ionospherementioning
confidence: 99%